Reality of The Application of The Laws and Regulations of The Coach Licenses for The Youth soccer’s at The Level of The Regional League of Annaba. - GUEMINI , Hafid; ABDELLI , Fateh (sports creativity, 2025)
The objective of the study is to know the reality of the application of the laws of training certificates to the coaches of the youth soccer teams in the soccer association of Annaba, as the subject is of direct importance to improve the mechanisms of soccer training in Algerian clubs in light of the variables of modern sports training, which requires first attendance Training competence at the highest level. A descriptive analytical approach was adopted to address the subject. At the same time, our sample of 130 coaches of different youth groups formed the regional clubs of the LRFA and holders of training licenses recognized by the Federation (FAF). The results of the research resulted in insufficient framing of the youth groups with licensed trainers due to the lack of assignment of the Algerian clubs on trained and legally qualified trainers according to the stipulated regulations as they do not possess the training certificates licensed by the National